Analisis Lingkungan Belajar dan Minat Belajar Peserta Didik Kelas XII RPL pada Mata Pelajaran Produk Kreatif dan Kewirausahaan di SMK Negeri 2 Karanganyar - Pratiwi, Intan Ajeng; Efendi, Agus; Sulistiyo, Budi (Universitas Sebelas Maret, 2024)
This research was conducted when carrying out direct experience practice against the background of the level of enthusiasm of students towards the varied subjects of creative products and entrepreneurship in order to improve the learning process that has been carried out in order to suit the conditions and needs of students. This research was carried out by making direct observations and distributing questionnaires to students. Processing the data using Microsoft Excel in the form of descriptive statistics. The results obtained in this study are that students feel that the learning environment at SMK Negeri 2 Karanganyar is appropriate, with the results obtained at 86.3594% while students' interest in creative products and entrepreneurship subjects is 78.0645%. These results can be concluded that students feel comfortable with the learning environment at SMK Negeri 2 Karanganyar and student interest can be increased in various ways, including by inviting students to be more active and improving the methods used to attract students' attention.